Tribes in Ladakh: A Study of Gara, Mon and Beda - Joldan, Sonam; Ladol, Chimat; Dolma, Rinchen; Nakdon, Tenzin; Spaldon, Jegmet (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
Although Ladakhi society is often seen as egalitarian, it involves complex layers of social stratification shaped by occupation and historical hierarchies. Among the most marginalised are the Gara (blacksmiths), Mon, and Beda (musicians), communities historically assigned low-status roles within the region’s socio-cultural framework. This study examines the socio-economic and cultural positioning of the Gara, Mon, and Beda within the broader context of Ladakhi society, highlighting the enduring influence of caste-like structures. It also looks into contemporary developments, education, rights awareness, and the increasing economic opportunities.